The Effect of Health Workers' Compliance with Medical Record Recording Standards Based on Permenkes No. 24 of 2022 on the Efficiency of Service Flow - Wasliati, Balqis (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Medical records are crucial documents in the healthcare system, as they contain all information related to a patient’s health, which can influence medical decision-making and support the quality of care and patient safety. Proper and standardized medical record documentation will facilitate the flow of services and minimize medical errors. Therefore, healthcare workers' compliance with medical record documentation standards is essential to enhance service efficiency in hospitals. Objective: This study aims to analyze the impact of healthcare workers' compliance with medical record documentation standards based on Minister of Health Regulation No. 24 of 2022 on service efficiency at RS Grandmed Lubuk Pakam. Methods: This research uses a quantitative descriptive correlational approach with purposive sampling technique involving 50 respondents, consisting of healthcare workers involved in medical record documentation. Data was collected using closed-ended questionnaires and analyzed using Pearson correlation and simple linear regression to determine the impact of compliance on service efficiency. Results: The findings show a strong positive relationship between medical record documentation compliance and service efficiency (r = 0.684; p = 0.000), with compliance contributing 46.8% to the improvement of service efficiency. Conclusion: Based on the results of the study, it can be concluded that there is a significant relationship between healthcare workers' compliance with medical record documentation standards and service efficiency at RS Grandmed Lubuk Pakam. Compliance with medical record documentation contributes 46.8% to the improvement of service efficiency. Therefore, it is recommended that the hospital enhance training for healthcare workers, conduct regular supervision, and implement an electronic medical record system to support the improvement of service quality and efficiency in the hospital's service flow. Therefore, it is recommended that the hospital increase training, routine supervision, and the implementation of an electronic medical record system to further enhance the quality of care and service efficiency.